"PSYCHOLOGY OF ALIENATION AND THE QUEST FOR BELONGING IN V S NAIPAUL'S 'HALF A LIFE' AND 'MAGIC SEEDS' - Dewangan, Nand Kumar; Khan, A. A.; Talat, Qamar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper examines the psychology of alienation and the quest for belonging in V.S. Naipaul's novels 'Half a Life' (2001) and 'Magic Seeds' (2004). Through a close analysis of the protagonist Willie Chandran's journey across continents and cultures, this study explores how Naipaul portrays the psychological impacts of displacement, cultural hybridity, and the search for identity in a postcolonial world. Drawing on theoretical frameworks from postcolonial studies, psychology, and literary criticism, the research investigates themes of rootlessness, cultural alienation, and the struggle for self-definition. Findings suggest that Naipaul's portrayal of Willie's experiences offers profound insights into the psychological complexities of postcolonial existence, highlighting the challenges of constructing a sense of self and belonging in a world marked by cultural dislocation and global mobility. This paper contributes to the growing body of literature on the psychological dimensions of postcolonial experience and offers new perspectives on Naipaul's later works.